WhatsApp as a Didactic Intervention Tool in the Teaching-Learning Process of Mathematics - Díaz-Flores, Rita (2025)
Objective. The purpose of this article is to determine if the use of the WhatsApp mobile application in the educational environment is appropriate as a pedagogical tool to strengthen the teaching-learning process of mathematics. Method. It is a descriptive type of research with a qualitative approach. A didactic strategy is used that involves the creation of a WhatsApp group as an educational resource in an introductory mathematics course at the university level. Likewise, a survey was carried out among the 30 students of different careers that were part of said group during the second semester of 2021. The obtained data were analyzed qualitatively by coding student responses and interactions within the WhatsApp group to identify key patterns and perspectives. Results. The students surveyed highlight two fundamental benefits: constant participation with feedback and the clarification of doubts in flexible hours. From the didactic strategy used, it is verified that WhatsApp improves communication and encourages collaborative learning. Conclusions. The use of the WhatsApp mobile application is favorable for the teaching-learning process, as long as it is used appropriately. The implications of this study suggest that while WhatsApp facilitates collaboration and flexible learning, it may require additional effort from teaching staff to manage interactions.